The survival of murine hepatitis virus (a surrogate of SARS-CoV-2) on conventional packaging materials under cold chain conditions - Xie, Tiancheng; Yang, Jiaxue; Fang, Chubin; Zhang, Jing; Lin, Hua; Zhu, Yalan; Tang, Tian; Wang, Chuan (Frontiers in Public Health, 2023)
The cold chain conditions have been suggested to facilitate long-distance transmission of SARS-CoV-2, but it is unclear how viable the virus is on cold chain packaging materials. This study used the MHV-JHM strain of murine hepatitis virus as a model organism to investigate the viability of SARS-CoV-2 on foam, plastic, cardboard, and wood sheets at different temperatures (-40°C, -20°C, and 4°C). In addition, the ability of peracetic acid and sodium hypochlorite to eliminate the MHV-JHM on plastic and cardboard sheets were also evaluated. The results indicate that MHV-JHM can survive on foam, plastic, or cardboard sheets for up to 28 days at -40°C and -20°C, and up to 14 days on foam and plastic surfaces at 4°C. Although viral nucleic acids were still detectable after storing at 4°C for 28 days, the corresponding virus titer was below the limit of quantification (LOQ). The study highlights that a positive nucleic acid test result may not indicate that the virus is still viable, and confirms that peracetic acid and sodium hypochlorite can effectively eliminate MHV-JHM on packaging materials under cold chain conditions.